Biological Evaluation of Synthesized N‐Cinnamoyl Phenothiazine Derivatives. Issue 46 (7th December 2018) - Selvendran, Suresh; J, Brindha; CS, Vasavi; Munussami, Punnagai; Pattusamy, Nithya; Chanda, Kaushik; MM, Balamurali; Rajendran, Saravanakumar
Abstract: N‐ Cinnamoyl phenothiazines were synthesized and characterized by various spectroscopic techniques including vibrational, nuclear magnetic resonance and mass spectrometry. The potential applications of these compounds as antioxidants and antibacterials were evaluated. Compound2 with –NO2 substituted cinnamoyl moiety in the phenothiazine ring nitrogen showed better antioxidant activity (77.8 μM for hydroxyl radicals and 85.0 μM for diphenyl picrylhydrazyl radicals). A moderate antibacterial activity (202‐330 μM) was observed for all the derivatives of phenothiazine against Gram‐positive and Gram‐negative bacteria, while the parent phenothiazine did not show any inhibitory activity up to 500 μM, indicating that the observed activity could be induced by the added cinnamoyl moiety. Nucleic acid and protein binding affinities were investigated for their applications as biomolecular probes. Both experimental and computational docking studies revealed an intercalative mode of binding with nucleic acids and 1:1 binding to bovine serum albumin. Abstract : The synthesized N ‐cinnamoyl phenothiazines possess antioxidant and antibacterial activity. They intercalatively bind to ct‐DNA (experimental methods and computational docking) and exhibited good binding affinity towards BSA protein.